Secure Programming with SAS: Mitigating Risks and Protecting Data Integrity - Yarlagadda, Vamsi Krishna; Pydipalli, Rajani (Engineering International, 2018)
This article examines the significance of safe programming with SAS (Statistical Analysis System) for risk mitigation and data integrity protection in data-driven environments. The study intends to investigate data protection strategies to improve application security, look at best practices for secure SAS coding, and identify prevalent security threats related to SAS applications. The review process is secondary data, with insights gleaned from online resources, industry reports, conference papers, and academic journals. Important discoveries show that SAS programs frequently have vulnerabilities, including SQL injection, cross-site scripting (XSS), and unsafe data handling. The best practices that have been established encompass data encryption, secure access controls, output encoding, parameterized queries, and input validation. The policy implications emphasize the significance of legislative frameworks for data protection and encouraging instruction in secure programming practices. This report emphasizes how important it is for businesses to use SAS for secure programming to protect sensitive data, abide by data protection laws, and defend against cyberattacks.
Keywords: SAS Programming; Secure Coding; Cybersecurity; Software Vulnerabilities; Information Protection